AB1149 Cystic fibrosis and inflammatory arthritis requiring immunosuppression: a worrying combination?. (12th June 2018) - Ibrahim, M.E.T.; Clarke, E.; Martin, K.; Peckham, D.; Jones, A.; Horsley, A.; Watson, P.; Freeston, J.E.
Abstract : Background: Inflammatory arthritis is a recognised complication of cystic fibrosis (CF) with an estimated prevalence of 2.3 [i] to 8.5% [ii] of CF patients. Cystic fibrosis associated arthritis (CFA) constitutes the majority of this, but other there may be other co-morbid rheumatic disease. Concerns about use of immunosuppression in the context of chronic pulmonary infection, and consequent risk of destabilisation, may limit use of these medications when clinically indicated. Immunosuppressive therapy is used in patients with CF lung disease who have inflammatory rheumatic disease, inflammatory bowel disease, or who have had a liver transplant for CF-related liver disease. Some data on those receiving immunosuppression post-transplant has been published and reassuringly reported fewer courses of intravenous antibiotics following transplant. [iii] Reports of immunosuppressants being used in other contexts, including arthritis, are more sporadic. Objectives: To assess prior use and safety outcomes of immunosuppressant therapy in adults with CF. Methods: A retrospective case note review of patients with CF receiving disease modifying anti-rheumatic drugs from 2 large adult CF centres (total >700 patients) from electronic records spanning 3–10 years. Results: 41 patients were identified: 7 post liver transplant, 1 with inflammatory bowel disease, 1 with IgA nephropathy; 32 with inflammatory arthritis. There was one possible case of increased pulmonary exacerbation associated with methotrexate; they remained on treatment at the time of the study. There was no evidence that immunosuppression resulted in a fall in lung function necessitating cessation of treatment in any of these cases. Three patients stopped hydroxychloroquine and 1 patient stopped methotrexate due to non-respiratory side effects. Four of 7 patients responded to treatment with sulfasalazine for inflammatory arthritis, 3 stopped due to non-respiratory side effects. Conclusions: No patients had immunosuppression stopped because of deterioration in lung disease. Steroids were not included in this analysis because duration and dose varied widely. However, it is important to note that they are frequently used in CF (particularly for allergic bronchopulmonary aspergillosis). Indeed 14% of all CF patients in these centres have had steroids in the last 6 months, of whom nearly half received a course of more than 6 months duration. Whilst our results are reassuring, the numbers remain small. Decisions must be made in conjunction with the multidisciplinary team, but CF in itself should not delay or stop treatment with immunosuppression where it is indicated. References: [1] Rush, P. J., A. Shore, et al. (1986). [2] Bourke, S., M. Rooney, et al. (1987). [3] Dowman, J. K., D. Watson, et al. (2012). Disclosure of Interest: None declared